Synthesis of Cu/TiO2 nanocomposite by gamma irradiation for enhanced photocatalytic activity - Vo, Thi Thu Nhu; Chu , Van Hien (Journal of Technical Education Science, 2020)
TiO2 doped with copper nanoparticles (Cu/TiO2) was prepared by g-irradiation method. The Cu/TiO2 nanoparticles were characterized using X-ray diffraction, transmission electron microscopy (TEM) and diffuse reflectance spectra (DRS). The photo-catalytic degradation of rhodamine B (RB) in the aqueous suspensions of TiO2 and Cu/TiO2 under visible light was carried out. Results showed that Cu/TiO2 catalysts was found to enhance photo-degradation efficiency of rhodamine B compared to pure TiO2. At 3.0% Cu content, the Cu/TiO2 photocatalyst exhibited the highest visible light photocatalytic activity. The higher activity of copper doped TiO2 is due to the enhancement of electron-hole separation by the electron trapping of copper particles.